Extracellular Vesicles and Their Potential Significance in the Pathogenesis and Treatment of Osteoarthritis - Mustonen, Anne-Mari (Pharmaceuticals (Basel), 2021)
Osteoarthritis (OA) is a chronic joint disease characterized by inflammation, gradual destruction of articular cartilage, joint pain, and functional limitations that eventually lead to disability. Join tissues, including synovium and articular cartilage, release extracellular vesicles (EVs) that have been proposed to sustain joint homeostasis as well as to contribute to OA pathogenesis. EVs transport biologically active molecules, and OA can be characterized by altered EV counts and composition in synovial fluid. Of EV cargo, specific non-coding RNAs could have future potential as diagnostic biomarkers for early OA. EVs may contribute to the propagation of inflammation and cartilage destruction by transporting and enhancing the production of inflammatory mediators and cartilage-degrading proteinases. In addition to inducing OA-related gene expression patterns in synoviocytes and articular chondrocytes, EVs can induce anti-OA effects, including increased extracellular matrix deposition and cartilage protection. Especially mesenchymal stem cell-derived EVs can alleviate intra-articular inflammation and relieve OA pain. In addition, surgically- or chemically-induced cartilage defects have been repaired with EV therapies in animal models. While human clinical trials are still in the future, the potential of actual cures to OA by EV products is very promising.